2011
DOI: 10.1152/jn.00686.2010
|View full text |Cite
|
Sign up to set email alerts
|

M1 and M4 Receptors Modulate Hippocampal Pyramidal Neurons

Abstract: Dasari S, Gulledge AT. M1 and M4 receptors modulate hippocampal pyramidal neurons. J Neurophysiol 105: 779 -792, 2011. First published December 15, 2010 doi:10.1152/jn.00686.2010. Acetylcholine (ACh), acting at muscarinic ACh receptors (mAChRs), modulates the excitability and synaptic connectivity of hippocampal pyramidal neurons. CA1 pyramidal neurons respond to transient ("phasic") mAChR activation with biphasic responses in which inhibition is followed by excitation, whereas prolonged ("tonic") mAChR activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
151
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(171 citation statements)
references
References 81 publications
18
151
2
Order By: Relevance
“…Rouse et al reported that the muscarinic inhibition of K + channels remained intact in the pyramidal neurons prepared from M 1 -knockout mice (Rouse et al, 2000). Dasari and Gulledge reported that carbachol-induced depolarization was reduced in neurons from either M 1 -knockout or M 3 -knockout mice, and was eliminated in M 1 /M 3 double-knockout mice (Dasari and Gulledge, 2011). These results are compatible with the idea that both M 1 and M 3 receptors are functional in pyramidal neurons.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Rouse et al reported that the muscarinic inhibition of K + channels remained intact in the pyramidal neurons prepared from M 1 -knockout mice (Rouse et al, 2000). Dasari and Gulledge reported that carbachol-induced depolarization was reduced in neurons from either M 1 -knockout or M 3 -knockout mice, and was eliminated in M 1 /M 3 double-knockout mice (Dasari and Gulledge, 2011). These results are compatible with the idea that both M 1 and M 3 receptors are functional in pyramidal neurons.…”
Section: Discussionsupporting
confidence: 54%
“…Instead of M 1 receptors, M 3 receptors were detectable in interneurons (Yamasaki et al, 2010). Using mice genetically lacking specific muscarinic receptor subtypes, receptor subtypes responsible for cholinergic modulation of ion channels have been identified in hippocampal pyramidal neurons (Dasari and Gulledge, 2011;Rouse et al, 2000). Rouse et al reported that the muscarinic inhibition of K + channels remained intact in the pyramidal neurons prepared from M 1 -knockout mice (Rouse et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the identity of the presynaptic mAChRs remains controversial. With the use of mAChR knockout mice, Dasari and Gulledge (2011) suggest that it is M 4 , not M 1 or M 2 , mAChRs; however, the sensitivity of eserineinduced presynaptic depression to 4-DAMP suggests a role for M 3 mAChRs. A presynaptic expression mechanism for eserine-LTD should be revealed by analysis of the PPR, an accepted indicator of alterations in presynaptic release probability (Dobrunz 2002;Kamiya and Zucker 1994).…”
Section: Discussionmentioning
confidence: 99%
“…There was examined effect of lesion of SI with kainate (1 μg/0.5 μL) on acetylcholine esterase (AChE) activity, muscarinic receptor number and subtypes in cerebral cortex at 1, 2 and 4 weeks [12] , and M 1 -and M 2 -receptors mediating opposite effects on neuromuscular transmission in rabbit vas deferens and concluded that twitch contractions of the rabbit vas deferens elicited field stimulation was inhibited by tetrodotoxin, guanethidine, bretylium and α, β-methylene-ATP, but that was unaffected by hexamethonium, physostigmine, 1,1-dimethyl-4-phenylpiperazinium and prazosin, therefore they resulted from ATP released postganglionic sympathetic nerve stimulation. Studies have been also regarding the agents which either act as agonist to the muscarinic receptors or antagonize its action [13] . Freschi finds that muscarinic agonists evoke a voltage dependent inward current in motoneurons of the lobster cardiac ganglion, and a number of drugs known to show muscarinic receptor subtype selectivity in mammals were used to determine the pharmacological profile of the muscarinic receptor on lobster motoneurons [14] .…”
Section: Muscarinic Receptorsmentioning
confidence: 99%